2020
DOI: 10.7160/aol.2020.120203
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Official Development Assistance on the Productivity of Agricultural Production in Ghana, Cameroon and Mali

Abstract: African economies depend largely on agriculture. Most people in Africa spend most of their lives in rural areas. Agriculture is an important sector of African industry and economy, it employs more than half of the population and accounts more than half of the national income. Due to population increase the food security remains an issue. In accordance of the lack of domestic capacities of African countries to deal with the problem, it is particularly important to increase assistance from developed countries. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…A significant number of papers reviewed, have established quite positive relationship between agriculture aid and agricultural sector growth but with a substitution effect between food and industrial crop production. Average output for cash or industrial crops for countries receiving Agricultural ODA have increased relative to food crops (Ssozi et al, 2018) though some studies have observed a positive correlation between cereal crop production and multilateral aid especially in Ghana and Mali (Blížkovský and Emelin, 2020). In general, the empirical review revealed an important link between foreign agricultural aid, growth and poverty reduction in sub Saharan African countries.…”
Section: Relation Between Development Aid and Agricultural Productivi...mentioning
confidence: 95%
“…A significant number of papers reviewed, have established quite positive relationship between agriculture aid and agricultural sector growth but with a substitution effect between food and industrial crop production. Average output for cash or industrial crops for countries receiving Agricultural ODA have increased relative to food crops (Ssozi et al, 2018) though some studies have observed a positive correlation between cereal crop production and multilateral aid especially in Ghana and Mali (Blížkovský and Emelin, 2020). In general, the empirical review revealed an important link between foreign agricultural aid, growth and poverty reduction in sub Saharan African countries.…”
Section: Relation Between Development Aid and Agricultural Productivi...mentioning
confidence: 95%
“…In Nigeria for example the agricultural share of GDP dropped from 36.9 percent in 2002 to 21.9 percent in 2019 (World Bank 2020). In fact, in Sub Saharan African countries in general, agricultural GDP had significantly dropped from 21.1 percent in 1994 to about 15.3 percent by the year 2019 (World Bank, 2020). The distribution of agricultural GDP on sub regional basis is even skewed.…”
Section: Investment In Agriculturementioning
confidence: 99%
“…Most scientists influence the diversification of agricultural production, cultivation of various species, and population growth on food security (Oppong, et al, 2014;Blizkovsky, et al, 2020). However, the study of the impact of hostilities on global food security in current conditions has not [48] Development of Organic Production in Ukraine: Potential, Current Threats and Consequences for Global Food Security received sufficient attention.…”
Section: Introductionmentioning
confidence: 99%